Polityka turystyczna w Polsce - Anszperger, Andrzej (Touristic Policy in Poland, 2009)
In most developed world economies, tourism is one of the most significant economic branches. Tourism creates on one hand workplaces, profits, revenues etc., and on the other - possibilities for people to rest after work, regenerate their health and wellbeing, develop their emotional and spiritual state. The accomplishment of these aims is possible thanks to proper economy policy and social policy of their country and local authorities. Unfortunately in Poland economic and social rank of tourism is underestimated, and tourism policy usually means a formal declaration which does not result in realization and using all the functions which brings tourism. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 489-497